Mycobacterial DNA-binding protein 1 is critical for long term survival of Mycobacterium smegmatis and simultaneously coordinates cellular functions - Shymaa Enany (Nature Portfolio, 2017)
Abstract Bacteria can proliferate perpetually without ageing, but they also face conditions where they must persist. Mycobacteria can survive for a long period. This state appears during mycobacterial diseases such as tuberculosis and leprosy, which are chronic and develop after long-term persistent infections. However, the fundamental mechanisms of the long-term living of mycobacteria are unknown. Every Mycobacterium species expresses Mycobacterial DNA-binding protein 1 (MDP1), a histone-like nucleoid associated protein. Mycobacterium smegmatis is a saprophytic fast grower and used as a model of mycobacterial persistence, since it shares the characteristics of the long-term survival observed in pathogenic mycobacteria. Here we show that MDP1-deficient M. smegmatis dies more rapidly than the parental strain after entering stationary phase. Proteomic analyses revealed 21 upregulated proteins with more than 3-fold in MDP1-deficient strain, including DnaA, a replication initiator, NDH, a NADH dehydrogenase that catalyzes downhill electron transfer, Fas1, a critical fatty acid synthase, and antioxidants such as AhpC and KatG. Biochemical analyses showed elevated levels of DNA and ATP syntheses, a decreased NADH/NAD+ ratio, and a loss of resistance to oxidative stress in the MDP1-knockout strain. This study suggests the importance of MDP1-dependent simultaneous control of the cellular functions in the long-term survival of mycobacteria.